Efficacy of Nd:YAG and diode laser transscleral cyclophotocoagulation in the management of neovascular glaucoma associated with proliferative diabetic retinopathy - O.V. Guzun; O.S. Zadorozhnyy; I.O. Nasinnyk; W. Chargui; Y. Oueslati; A.R. Korol (Ukrainian Society of Ophthalmologists, 2024)
Background: Transscleral cyclophotocoagulation (TSCPC) is most commonly used in patients with neovascular glaucoma (NVG) associated with proliferative diabetic retinopathy (PDR) in whom maximal hypotensive medications have failed to reduce intraocular pressure (IOP) to the desired level, and glaucoma surgery cannot be carried out. Options for CPC can be performed using a neodymium:yttrium-aluminum-garnet (Nd:YAG) laser or diode laser. Purpose: To compare the efficacy of TSCPC performed with the 1,064-nm Nd:YAG laser versus 810-nm diode laser in patients with painful NVG associated with PDR over a 12-month follow-up period. Material and Methods: A prospective cohort study was carried out on 58 type 2 diabetics (58 eyes) who received a 1,064-nm Nd:YAG laser TSCPC or 810-nm diode laser TSCPC for painful NVG associated with PDR, with regular follow-up visits over 12 months and had no previous history of treatment with CPC. IOP between 6 and 21 mmHg (or a reduction in IOP of ≥ 30% from baseline IOP) and no ocular pain at 12 months was the primary outcome measure. Results: The success rate at 12 months was 75% and 77% for eyes that received Nd:YAG laser TSCPC and diode laser TSCPC, respectively (p = 0.86). In the Nd:YAG laser TSCPC and diode laser TSCPC groups, the IOP reduced by 46% and 45%, respectively (p = 0.34) from baseline values of 38.0 mmHg and 36.0 mmHg, respectively (p = 0.96) at month 12 after TSCPC. At month 12 after CPC, the BCVA in patients with preserved pattern vision improved in both groups (p = 0.41). The rate of ocular complications was, however, higher in the diode laser TSCPC group (71% versus 33%, p = 0.004). Conclusion: Nd:YAG laser TSCPC resulted in a reduction in IOP to ≤ 21 mmHg at month 12 in 75%, and diode laser TSCPC, in 77% of patients with NVG associated with PDR. The number of sessions required for treatment success was 3.2 times larger for Nd:YAG laser CPC than for diode laser CPC. Both these types of CPC are safe and can be repeatedly used to improve treatment efficacy.